Dessiner son terrain pour le ressentir - Anne-Adélaïde Lascaux; Antoine Rigaud (EchoGéo)
Although researchers are increasingly incorporating drawing and comics into their methodological toolboxes, these tools remain on the margins of most scientific demonstrations. In contrast, this article revisits a research experiment using drawings in a geographical demonstration, conducted in association with Antoine, a researcher and a comics author, during my PhD. Together, we argue that graphic works are useful methodological tools for scientific demonstration. Drawings and comics highlight scientific data and preserve the integrity of the interviewees on the field. Moreover, the emotion that emerges from these works halfway between art and science is also a vector of information on a sensitive mode.